Observation of two resonances in the [lambda]0b π± systems and precise measurement of [sigma]±b and [sigma][star] ±b properties - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Kecke, Matthieu; et al. (Physical review letters, 2019)
The first observation of two structures consistent with resonances in the final states Λ0bπ− and Λ0bπ+ is reported using samples of pp collision data collected by the LHCb experiment at √s=7 and 8 TeV, corresponding to an integrated luminosity of 3 fb−1. The ground states Σ±b and Σ*±b are also confirmed and their masses and widths are precisely measured.
Im Titel werden die Buchstaben Lambda, Sigma und star als griechische Buchstaben dargestellt
Im Titel sind "+" und "-" untereinander geschrieben: "plus" hochgestellt, "minus" tiefgestellt
Im Titel sind "0" und "b" untereinander geschrieben: "0" hochgestellt, "b" tiefgestellt
Im Titel ist "star" hochgestellt
LHCb Collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, A. Piucci, P. Seyfert, M. Stahl, S. Stemmle, N. Skidmore, U. Uwer, A. Zhelezov [und weitere] (LHCb collaboration)